Pleurochaete squarrosa (Brid.) Lindb. as an alternative moss species for biomonitoring surveys of heavy metal, nitrogen deposition and δ15N signatures in a Mediterranean area. (January 2016) - Izquieta-Rojano, S.; Elustondo, D.; Ederra, A.; Lasheras, E.; Santamaría, C.; Santamaría, J.M.
Highlights: Biomonitoring in Mediterranean areas: Hypnum cupressiforme vs Pleurochaete squarrosa . The soil dust and the tree crown leaking influenced the elemental content in mosses. Both mosses depicted similar heavy metal deposition patterns for all sampling sites. Pleurochaete squarrosa was better than Hypnum cupressiforme to discriminate oxidized and reduced N sources. Simultaneous use of both species is possible for nitrogen monitoring surveys. Abstract: There is a significant lack of data in biomonitoring surveys from southern Europe and other Mediterranean biogeographic areas. This scarcity is mainly due to the impossibility of finding the commonly recommended species in a great portion of these dry environments. The present work was carried out with the aim of assessing the validity of the moss Pleurochaete squarrosa (Brid.) Lindb. (PS) as a feasible alternative in these regions. The study was developed in the Mediterranean area of Navarra, in northern Spain, where the response of PS to multiple atmospheric pollutants (N, Al, As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sb, Ti and Zn) was compared to that of Hypnum cupressiforme Hedw. (HC), an accepted and widely used species in biomonitoring surveys. Moreover, N isotopic signatures from both species were studied to evaluate their effectiveness when identifying nitrogen emission sources. The enrichment factor (EF) approach was used to evaluate the heavy metal uptake, showing a similar behaviour for both species: low EF for Al, As, Cr and Fe; intermediate for Mn, Ni, Pb and Sb; and high for Cd, Cr, Hg and Zn. Equally, both species depicted the same N deposition patterns across the study area. However, regarding δ 15 N, PS gave a more congruent picture with the location of the main sources of N emissions in the area. These data suggest that PS may be a suitable biomonitor to fill the aforementioned gaps in Mediterranean biogeographic areas.